A escrita matemática em uma turma de 6ª série do ensino fundamental - Flavia Cristina Figueiredo Goura (2008)
This work focuses some texts that were written by the students during Mathematics classes when the words prevailed in relation to the mathematical symbolic. Those texts were produced within a sixth grade classroom of a public Elementary School in Belo Horizonte. The students accomplished many written mathematical activities that were proposed by their Teacher and the Researcher. The written mathematics concept, which represents our investigation subject matter, as well as the ways for classifying that writing, were outlined from our studies on theoretical references of the Mathematical Education research field. The analyses that were undertaken have enabled us to identify four categories of mathematical writing utilized by the students: to record, to express themselves, to explain and to translate. By characterizing the categories apiece considering the language functions, the mathematical genres and the uses of the mathematical writing the aim is to put emphasis, mainly, on how the students write in the classes of Mathematics, utilizing a non- exclusively mathematical language. This way, it is possible to consider that our investigation may offer contributions for research in Mathematics Education, in so far as it represents a perspective of answer for the gap in the research about the studentsmathematical writing. In the same way, we believe this investigation may provide contributions for the work with school Mathematics in, since its results nurture the reflection about writing in Mathematics classrooms.